Psychrophilic superoxide dismutase from Pseudoalteromonas haloplanktis: biochemical characterization and identification of a highly reactive cysteine residue - CASTELLANO, I.; DI MARO, A.; RUOCCO, M. R.; CHAMBERY, A.; PARENTE, A.; DI MARTINO, M. T.; PARLATO, G.; MASULLO, M.; DE VENDITTIS, E. (Biochimie, 2006)
A psychrophilic superoxide dismutase (SOD) has been characterized from the Antarctic eubacterium Pseudoalteromonas haloplanktis (Ph). PhSOD is a homodimeric iron-containing enzyme and displays a high specific activity, even at low temperature. The enzyme is inhibited by sodium azide and inactivated by hydrogen peroxide; it is also very sensitive to peroxynitrite, a physiological inactivator of the human mitochon- drial Mn-SOD. Even though PhSOD is isolated from a cold-adapted micro-organism, its heat stability is well above the maximum growth temperature of P. haloplanktis, a feature common to other Fe- and Mn-SODs. The primary structure of PhSOD was determined by a combination of mass spectrometry and automated Edman degradation. The polypeptide chain is made of 192 amino acid residues, corresponding to a mole- cular mass of 21251 Da. The alignment with other Fe- and Mn-SODs showed a high amino acid identity with Fe-SOD from Vibrio cholerae (79%) and Escherichia coli (70%). A significant similarity is also shared with human mitochondrial Mn-SOD. PhSOD has the unique and highly reactive Cys57 residue, located in a variable region of the protein. The three-dimensional model of the PhSOD monomer indicates that Cys57 is included in a region, whose structural organization apparently discriminates between dimeric and tetrameric SODs. This residue forms a disulfide adduct with β-mercaptoethanol, when this reducing agent is added in the purification procedure. The reactivity of Cys57 leads also to the for- mation of a disulfide bridge between two PhSOD subunits in specific denaturing conditions. The possible modification of Cys57 by physiolo- gical thiols, eventually regulating the PhSOD functioning, is discussed.